A palynological study and molecular analysis of the Desmodium procumbens group (Leguminosae-Papilionoideae) in Mexico. Issue 3 (4th May 2017) - González-Vázquez, Rocío; Ramírez-Arriaga, Elia; Martínez-Hernández, Enrique; Jiménez-García, Luis Felipe; Agredano-Moreno, Lourdes Teresa; Delgado-Salinas, Alfonso
Abstract: Desmodium diversity has been mainly classified using fruit characters, and because of variability in these and other characters, the taxonomy has sometimes been problematic and thus, there is a need for clarification and taxonomic reassessments. This is the case for the Desmodium procumbens group, where several infraspecific taxa have been named. The phylogenetic relationships among taxa referred to this group is unknown, and the taxonomic status has been recently revised only for some of the taxa. In this study, pollen morphology and ultrastructure of D. neomexicanum, D. procumbens var. procumbens, D. procumbens var. exiguum, D. procumbens var. longipes and D. procumbens var. transversum, belonging to the Mexican Desmodium procumbens group, were examined using light, phase-contrast, scanning electron and transmission electron microscopy, in order to establish palynological characters that might contribute to a better taxonomic resolution. Pollen grains are tricolporate, radiosymmetric, oblate spheroidal to prolate spheroidal shape, with lalongate endoapertures and rugulate exine with foveolae between rugulae. The exine is tectate with a columellate and/or granulate structure. The absence of a fastigium, features of exine sculpture, a colpus membrane and infrastructure mainly dominated by granules differentiate the pollen grains of the varieties exiguum and transversum from the other taxa studied. Pollen traits and sequence data provide evidence for separating D. neomexicanum from species D. procumbens . In general, the result from the pollen analysis is congruent with results obtained from a preliminary molecular analysis of this group.